Estimation of reservoir rock and fluid properties - Ganat, T.A.-A.O. (Springer, 2020)
Reservoir rock and fluid properties are the vital parameters that control the estimation of the original oil and gas in place and the recoverable oil and gas. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.